Comparison of the spatio-temporal distribution and composition of meiofauna with focus on nematodes in a NaGISA rocky shore site in Southern Guimaras between theyears 2016 and 2017. - Timbancaya, Edward P. (2019.)
The spatial and temporal variations of meiofaunal communities with focus on nematode assemblages in a rocky shore site in Taklong Island National Marine Reserve, Southern Guimaras between the years 2016 and 2017 were examined. Field sampling was done on September 2016 and September 2017, following the NaGISA sampling protocol with three 27-meter transects namely THT (high tide), TLT (low tide), TST (subtidal at 1m depth) laid parallel to the shore. The overall mean meiofaunal desnsity for 2016 was 10, 504 (± 1, 315.97) ind∙m^(-2), composed of organisms belonging to 15 taxa with nematodes (50.04%), harapacticoid copepods (14.90%), and syllid polychaetes (11.53%) being the top three taxa. For the samples in the year 2017, the overall meiofaunal density was 5, 202.67 (± 650.17), composed of organisms belonging to 15 taxa with nematodes (50.00%), harpacticoid copepods (15.90%), and syllid polychaetes (13.29%) being the top three taxa. The meiofaunal density was highest in the subtidal transect for 2016, with a shift to the high-tide transect in 2017 due to temporal temperature variations. This is supported by the significant difference (t = 0.035) found between the meiofaunal densities in both of the 2016 and 2017. There were 13 nematode families identified for both 2016 and 2017. The most abundant nematode family was Desmodoridae for both 2016 (28.31%) and 2017 (57.33%). However, one-way ANOVA showed that there were no significant differences found between nematode family distribution and tidal levels for both of the years 2016 (F = 0.160, P=0.853) and 2017 (F=0.001, P = 1.000). The nematode assemblage was dominated by epigrowth feeders (2A) for both 2016 (64%) and 2017 (79%), mainly represented by members of the families Desmodoridae and Chromadoridae. Meanwhile, macroalgal biomass showed negative correlations with nematode densities for both of the years 2016 (R = -0.965) and 2017 (R = -0.586).
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2019.
Keywords: Meiofauna -- NaGisa Rocky Shore -- Southern Guimaras -- 2016 and 2017.